Preparation of aminoethyl glycosides for glycoconjugation - Robert Šardzík; Gavin T. Noble; Martin J. Weissenborn; Andrew Martin; Simon J. Webb; Sabine L. Flitsch (Beilstein Journal of Organic Chemistry, 2010)
The synthesis of a number of aminoethyl glycosides of cell-surface carbohydrates, which are important intermediates for glycoarray synthesis, is described. A set of protocols was developed which provide these intermediates, in a short number of steps, from commercially available starting materials.